Performance of groundnut (Arachis hypogaea) under different phosphorus management options in semi-arid environment of Rajasthan - YADAV, M R; KUMAR, YOGENDRA; POONIYA, VIJAY; GUPTA, K C; SAXENA, RANI; GARG, N K; SINGH, AJEET (The Indian Journal of Agricultural Sciences, 2019)
The present field investigation was carried out during kharif season of 2015, 2016 and 2017 at Rajasthan Agricultural Research Institute (RARI), Durgapura, Jaipur to evaluate the effect of various phosphorous (P) management options on growth, productivity and economics of groundnut (Arachis hypogaea L.). The experiment was carried out in a randomized complete block design with 10 P management practices. Results revealed application of 5 t farmyard manure (FYM) + 50% chemical P + DGRC–1 and 5 t FYM + 100% chemical P + DGRC–1 increased dry matter accumulation by 47.5% and 48.72% (35 days after sowing, DAS), 38.6% and 34.6% (70 DAS) and 38.9% and 35.1% (at harvest) over no P fertilization. Application of 5 t FYM + 50% chemical P + DGRC–1 enhanced crop growth rate (CGR) by the magnitude of 19. 8%–47. 5% (0–35 DAS), 12. 5%– 36. 3% (35–70 DAS), and 13. 4%5–39. 5% (70 DAS–at harvest) compared to control and 5 t FYM, 5 t FYM + DGRC–1 and 5 t FYM + DGRC–2 plots. The maximum number of pods/plant, pod weight/plant, test weight and shelling% were also registered with application of 5 t FYM +50% chemical P + DGRC–1. With respect to yields, application of 5 t FYM + 50% chemical P + DGRC–1 resulted in the maximum pod (5. 99 t/ha) and kernel (4. 29 t/ha) yields. The maximum net returns and B:C ratio were recorded when the crop was fertilized with 5 t FYM + 50% chemical P + DGRC–1. Finally, it can be concluded that integrated P management in groundnut using 5 t FYM + 50% chemical P + DGRC–1 can be advocated as sustainable P management strategy for enhancing productivity and profitability under semi-arid conditions of Rajasthan.